Isolation of a myotoxin from Bothrops asper venom: Partial characterization and action on skeletal muscle - Ownby, Charlotte L. (1984)
A myotoxic phospholipase has been isolated from Bothrops asper venom by ion-exchange chromatography on CM-Sephadex followed by gel filtration on Sephadex G-75. The toxin is a basic polypeptide with an estimated molecular weight of 10,700. It has both phospholipase A and indirect hemolytic activities, but is devoid of proteolytic, direct hemolytic and hemorrhagic effects. When injected i.m. into mice the toxin induces a rapid increase in plasma creatine kinase levels and a series of degenerative events in skeletal muscle which lead to myonecrosis. The toxin induces an increase in intracellular calcium levels and is able to hydrolyze muscle phospholipids in vivo. Pretreatment with the calcium antagonist verapamil failed to prevent the myotoxic activity. It is proposed that B. asper myotoxin causes cell injury by disrupting the integrity of skeletal muscle plasma membrane and that myotoxicity is at least partially due to the phospholipase A activity of the toxin.